(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: The only method to stop the progression of glaucoma is to decrease intraocular pressure (IOP). Nesiritide is a natriuretic peptide that is effective in reducing blood pressure via his vasodilator action, which may be effective in reducing IOP. Objective: To evaluate the efficacy of nesiritide 0.005% eye drops on IOP of ocular normotensive and betamethasone-induced ocular hypertensive rabbits in comparison with that of latanoprost 0.005% eye drops; besides, to study the safety profile of nesiritide eye drops. Methods: This study included 36 male rabbits; 18 rabbits represented the ocular normotensive groups (control, latanoprost, and nesiritide) and the other 18 rabbits represented betamethasone-induced ocular hypertension groups (vehicle, latanoprost, and nesiritide). Tested drugs instilled as one drop twice daily for 7 days in normotensive and hypertensive left eye. The IOP was measured with the aid of Schiötz tonometer. Other examined parameters were pupil diameter, light pupillary reflex, corneal sensation reflex, and conjunctival redness which were recorded before starting the experiment and then daily before and after drug application for one week. Results: This study revealed that nesiritide eye drops significantly reduced IOP since the 3rd day in both normotensive and steroid-induced ocular hypertensive model; yet, this effect was less potent than that of latanoprost eye drops. Nesiritde eye drops did not induce significant changes in the other examined parameters. Conclusion: This study revealed the efficacy and apparent safety of nesiritide 0.005% eye drops in lowering IOP in both ocular normotensive and betamethasone-induced ocular hypertensive rabbits. Keywords: Nesiritide, Latanoprost, intraocular pressure, glaucoma Citation: Abdul-Jabbar MA, Al-Zubaidy AA. Ocular hypotensive effects of nesiritide 0.005% eye drops on ocular normotensive and betamethasone-induced ocular hypertensive rabbits. Iraqi JMS. 2025; 23(1): 155-163. doi: 10.22578/IJMS.23.1.18